2014
DOI: 10.5530/pj.2014.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Oral Acute Toxicity Studies of b-mangostin Isolated from Cratoxylum arborescens

Abstract: Introduction:The objective of this study was to investigate the cytotoxicity and oral acute toxicity of β-mangostin isolated from Cratoxylum arborescens. Material and methods: Healthy male and female ICR mice (8 weeks) were fed orally with 250 and 500mg/kg of β-mangostin. Body weight of each animal was measured and any gross behavioral change was observed daily. Hematological and clinical biochemical parameters as well as histopathological analysis were carried out on 15 th day. The level of oxidative stress w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Table 1 represents 1 H-NMR, 13 C-NMR and DEPT of β-mangostin. 1 H-NMR and 13 C-NMR result was compared with reported data by Sen et al [14], Al-Massarani et al, [15] and Syam et al [16] ] appeared as green and dark brown complex respectively. They are stable at room temperature.…”
Section: Structural Elucidation Of β-Mangostinmentioning
confidence: 70%
“…Table 1 represents 1 H-NMR, 13 C-NMR and DEPT of β-mangostin. 1 H-NMR and 13 C-NMR result was compared with reported data by Sen et al [14], Al-Massarani et al, [15] and Syam et al [16] ] appeared as green and dark brown complex respectively. They are stable at room temperature.…”
Section: Structural Elucidation Of β-Mangostinmentioning
confidence: 70%
“…The purity of isolated -mangostin was 98% determined from HPLC analysis. -mangostin 1 H-NMR and 13 C-NMR data were compared with reported data by Shen et al[15]; Al-Massarani et al[16] and Syam et al[17]. The 1 H NMR spectrum showed the presence of one chelated hydroxyl group at  13.66.…”
mentioning
confidence: 75%
“…The results showed that no acute toxicity was identified in experimental rats. The results showed that oral administration of mangostin did not decrease the growth rate, hematology and clinical biochemical parameters and did not alter oxidative stress biomarkers [33]. Histologically, there are no pathological changes in the liver and kidneys [33].…”
Section: Compoundsmentioning
confidence: 91%